The Oxford history of the laws of England. vol. 2, 817-1216 - Hudson, John. (Oxford : Oxford University Press, 2012)
By 1216 the foundations of the English common law had been laid. This book assesses the development of law and society during the preceding three centuries, including the Norman Conquest of 1066. It analyses the great legacy of the Anglo-Saxon realm, the impact of Norman custom, and the energetic contribution of the twelfth-century kings
Keywords: Law -- England -- History -- To 1500.; Law, Medieval; historia; keskiaika; lait; Iso-Britannia